Development of a therapists' self-report measure of pluralistic thought and practice: the Therapy Pluralism Inventory. Issue 5 (20th October 2017) - Thompson, Allison; Cooper, Mick; Pauli, Regina
ABSTRACT: This study aimed to develop a self-report measure of pluralistic thought and practice. Following pilot development, a 23-item inventory was placed on an online survey site, and 474 participants satisfactorily completed the measure. Respondents were trainee or qualified therapists, predominantly female, based in the UK, and of a humanistic or integrative/eclectic orientation. A principal components analysis resulted in two scales, Pluralistic Philosophy and Pluralistic Practice, which had good internal consistency (Cronbach's α = .72 and .80, respectively). Confirmatory factor analysis showed good model fit for this two factor solution. The Therapy Pluralism Inventory (TPI) has potential for use in training and research, although additional validity and normative data are needed.